A Real‐time PCR assay for rapid identification of Helicoverpa armigera (Lepidoptera: Noctuidae) from closely related species. (11th November 2021) - Thomas, Asha; Li, Dongmei; Gunawardana, Disna; Flynn, Alan
Abstract: The bollworm, Helicoverpa armigera, is one of the most important agricultural pests in the world. Diagnosis of this species morphologically is difficult from the similar species H. assulta, H. punctigera and H .  zea as the adults are identified based on genitalia morphology and larval identification is limited due to shared morphological characters. To provide an accurate diagnosis of New Zealand border interceptions, we have developed a real‐time PCR assay to identify H .  armigera from commonly occurring exotic Helicoverpa species, H. assulta and H .  zea . Preliminary studies, using the already available real‐time ITS2 primer–probe detecting H .  armigera and H .  zea tested on samples obtained from NZ border interceptions and from overseas showed cross reactions with low intensities among H .  armigera, H. assulta and H .  zea . This prompted PHEL to develop a new real‐time PCR assay to accurately identify H .  armigera . The newly designed primer and probe were optimized, and the assay demonstrated its specificity to H .  armigera with no false positives observed in the non‐target species tested in this study. The specificity of the assay was tested against 64 samples of Lepidoptera from 14 countries including 48 Helicoverpa samples. The sensitivity of the assay showed it can detect up to 1 copy/µl of the DNA fragment. Therefore, this assay can be used for rapid detection of H .  armigera, which is imperative in quarantine application to determine the presence of exotic species regardless of its life stage.